103k views
2 votes
If g (x) = 2x + 2, find g (a + h) - g (a)

User Jpgrassi
by
5.4k points

1 Answer

3 votes

Answer:


g(x) = 2x+2

Let's find g(a+h):


g(a+h)=2*(a+h) +2= 2a +2h +2

And now let's find g(a)


g(a)= 2a+2

And now finally:


g(a+h) = 2a +2h +2 -2a-2 = 2h +2-2= 2h

Explanation:

We have the following function given:


g(x) = 2x+2

Let's find g(a+h):


g(a+h)=2*(a+h) +2= 2a +2h +2

And now let's find g(a)


g(a)= 2a+2

And now finally:


g(a+h) = 2a +2h +2 -2a-2 = 2h +2-2= 2h

User Blacksad
by
6.2k points